"Al-Quds" fī Manẓūri al-Maʿna al-Irsyādī wa al-Taʾwīlī ʿinda Rīfātīr fī Syiʿri nizār Qabbānī - Rosi, Khoirur; Kainuzah, Fatkhan Alief (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
Poetry is processing words into a beautiful sentence, in which the word is not like the words conveyed in everyday life. In this case poetry contains implied meaning in it so that in interpreting a poem requires thinking that is sensitive to the object in question. Riffaterre argues that poetry expresses something indirectly or says something by meaning something else. This study carries out the meaning of poetry by using Riffaterre's semiotic theory. In finding the significance of poetry, the researcher uses the analytical method proposed by Riffaterre, namely heuristic reading and hermeunitic reading. In heuristic reading, the researcher found various ungrammaticalities that hindered understanding. According to Riffaterre, to overcome these obstacles the researcher must continue reading at the second level, namely hermeneutic reading.In the second level of reading, ungrammatical is not a hindrance but a guide to significance. The object of this research is Nizar Qobbani's poem entitled "Al-Quds". Nizar Qobbani's poetry which is examined in this study contains a human element to the tragedy that occurred in Palestine. The results of the analysis show that the tragedy that occurred in Palestine as an ungrammatical appearance in the poem has become a guide to significance.